Chemical communication of handling stress in fish - Gil Barcellos, Leonardo Jose; Volpato, Gilson Luiz [UNESP]; Barreto, Rodrigo Egydio; Coldebella, Ivanir; Ferreira, Daiane (Pergamon-Elsevier B.V. Ltd, 2011)
We investigated whether juveniles of the nocturnal fish jundia (Rhamdia quelen) and the diurnal fish Nile tilapia (Oreochromis niloticus) are able to chemically communicate stress to conspecifics. Groups of 8 fish were reared in tanks under recirculated water (water exchanged among all the tanks) for each species. Fish were handled in half of the tanks (stressor fish) and whole-body cortisol concentrations were compared among handled fish, non-handled fish exposed to water from the handled fish, and non-handled control fish held with no water communication. For each treatment cortisol concentrations were determined before exposure to the stressor (basal levels) and after 1, 2, 4, 8, and 24 h. Basal levels of cortisol confirmed fish were unstressed in the beginning of the experiment. Cortisol was increased in the stressor fish 1 h after handling. Fish receiving water from the stressor fish increased cortisol levels later (2 h after the stressor fish were handled). As the isolated control group maintained cortisol levels unchanged throughout the experiment, we concluded that some chemical factor was released by the stressed fish in the water and thus stressed the conspecifics. This pattern was similar for both unrelated species, thus suggesting that this communication might have evolved earlier in fish and reinforcing the biological value of this kind of information. Published by Elsevier B.V.
Keywords: Chemical communication; Stress; Fish; Cortisol